2019
DOI: 10.1002/bjs.11293
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a nomogram to predict the risk of cancer in patients with intraductal papillary mucinous neoplasm and main duct dilatation of 10 mm or less

Abstract: Background Intraductal papillary mucinous neoplasm (IPMN) is premalignant pancreatic lesion. International guidelines offer limited predictors of individual risk. A nomogram to predict individual IPMN malignancy risk was released, with good diagnostic performance based on a large cohort of Asian patients with IPMN. The present study validated a nomogram to predict malignancy risk and invasiveness of IPMN using both Eastern and Western cohorts. Methods Clinicopathological and radiological data from patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 22 publications
1
27
2
Order By: Relevance
“…The overall performance of the LR models was 0.725 (see Fig. 3), slightly lower than previous studies (0.72-0.85) 3,5,11 . To increase the performance, we hypothesized that prediction models based on different statistical techniques, such as the ML technique, can be potentially used as an alternative method for prediction and classification 12 .…”
Section: Discussioncontrasting
confidence: 62%
“…The overall performance of the LR models was 0.725 (see Fig. 3), slightly lower than previous studies (0.72-0.85) 3,5,11 . To increase the performance, we hypothesized that prediction models based on different statistical techniques, such as the ML technique, can be potentially used as an alternative method for prediction and classification 12 .…”
Section: Discussioncontrasting
confidence: 62%
“…This nomogram was based on a large eastern cohort, includes both radiologic and laboratory findings, and it has the advantage of easy access. In addition, studies have recently been published, showing that it also has good external validity for western cohorts [15]. The current study demonstrated the MP-N to have good calibration with the Hosmer-Lemeshow goodness-of-fit test, and that it had a good AUC value of 0.8033 in patients with IPMN and main duct dilatation of 10 mm or less.…”
Section: Discussionsupporting
confidence: 62%
“…Using CT or MRI features only, the presence of an enhancing mural nodule, main pancreatic duct size, abrupt main pancreatic duct caliber change, and lymphadenopathy were more common in malignant than benign IPMNs resulting in AUCs of 0.83 and 0.86 with CT and MRI, respectively [52]. Besides recommendations, nomograms have been tested and validated in Eastern and Western patients, with AUC for combined cohorts in the range of previous works (0.776) [53].…”
Section: Discussionmentioning
confidence: 93%